RAGAM DAN ARAH PERTANYAAN PENYIDIK DALAM BERITA ACARA PEMERIKSAAN PERKARA PIDANA ANAK - Andika Dutha Bachari; Dadang Sudana; Wawan Gunawan (Masyarakat Linguistik Indonesia, 2018)
This study aims to report a study on the patterns of Indonesian police strategies in examining criminal cases involving children. The ability to ask questions is instrumental for the investigators. The variety, content, and direction of the investigators’ questions determine the value of information obtained from investigations(see Clarke & Milne, 2001). By using Strauss and Corbin’s qualitative paradigm, Glacer’s ground theory as well as Milne’s analytical frameworks, the present study has revealed that despite the fact that police investigation reports contained a lot of unproductive questions that might lead to unproductive answers, they compensated these with other investigative questioning strategies to reveal more information. Therefore effectiveness of questioning is more determined by these follow-up strategies than by the initial questions addressed to the suspects.